Hubungan Dukungan Keluarga dengan Kelengkapan Imunisasi Dasar pada Balita di Wilayah Kerja Puskesmas Darul Imarah Aceh Besar - Siska Silvia; Fauziah Fauziah; Mansuriza Mansuriza (Lembaga Pengembangan Kinerja Dosen, 2025)
Basic immunization helps to prevent infectious diseases in toddlers. It increases immunity and reduces morbidity and mortality. However, full basic immunization coverage is low in several areas, including the Darul Imarah Health Center, Aceh Besar. Family support is considered one of the influencing factors. This support can be emotional, informational, instrumental, or appraisal. The purpose of this study was to determine the relationship between family support and the completeness of basic vaccinations for toddlers in the service area of ​​the Darul Imarah Community Health Center in Aceh Besar. This study used a quantitative cross-sectional design. Using a probability random sampling method, the sample size was 90 respondents out of 817 respondents in the population. The research was conducted from May 5th to 24th, 2025. The study used both bivariate and univariate analyses. The data collection was analyzed using the Chi-Square test. The results showed a relationship between family support and toddler immunization completion, with a P-value of 0.003 (p<0.05). The conclusion indicates a relationship between family support and immunization completion. Therefore, this research provides insight for the family's role in improving basic immunization coverage for toddlers. The findings may help the Darul Imarah Health Center and healthcare workers design strategies for socialization and family support to reach complete immunization targets.